The Organizational Attraction at Company-owned University - Rocky, Rocky; Dahesihsari, Rayini (International Research Journal of Business Studies, 2016)
This study took place in a university established by a company. The aim of this study is to investigate factors which may influence the university students’ affect toward the parent company. The construct of interest is organizational attraction, which is the positive attitude of an individual regarding an organization. A combination of qualitative and quantitative methods were used in this study. The total number of participants in this study was 161 (60 males, 101 females; 84 students who never worked before, 64 worked part time, 13 have worked full time). Results showed the students had neutral attitude toward the organization as a workplace. This indicates that the students do not necessarily prefer the parent company to other companies. Other findings showed the first year students have higher level of organizational attraction compared to final year students, presumably due to word of mouth by the lecturers.